Notary Ethics in the Transfer of Fictitious Land Rights: The Role of Notaries in Preventing Property Fraud in the Case of Nirina Zubir Fake Certificates - Dito Aditia Darma Nst; Nabilah Syaharani; Lucas Medianov Grand; Citra Nurdiana; Ziqra Elfhadjri; Defri Dwi Saputra; Rizki Nanda Fauzi Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The land mafia case involving forged certificates belonging to Nirina Zubir’s family highlights weaknesses in the integrity, professionalism, and supervision of notary practices in the transfer of land rights. The involvement of notaries in preparing deeds and legalizing false documents shows that their function as public officials responsible for ensuring the authenticity of identities and the formal validity of documents was not carried out according to legal and ethical standards. This situation causes significant losses for landowners and threatens public legal certainty, making an in-depth study of notary ethical accountability necessary. This research uses a normative juridical method with three approaches. First, a legislative approach to examine notary obligations, authority, and limits of responsibility under the Notary Law, Notary Code of Ethics, PPAT regulations, and land laws. Second, a case approach analyzing the chronology and role of notaries in the forgery of Nirina Zubir’s land certificates. Third, a conceptual approach using Hans Kelsen’s theory of legal liability and Gustav Radbruch’s theory of legal certainty. The findings show that notaries who facilitate fictitious land transfers commit ethical, administrative, and criminal violations by ignoring prudence, integrity, objectivity, and identity verification duties. According to Kelsen, violating legal norms results in sanctions as normative accountability. Radbruch’s perspective emphasizes that such practices undermine legal certainty. Strengthening ethics, improving supervision, and enforcing strict verification are essential to prevent property fraud.